ALGORITHM CONSTRUCTION AND SOLVING OF OPTIMAL MANAGEMENT PROBLRM OF FINANCIAL SYSTEM: ALGORITHM CONSTRUCTION AND SOLVING OF OPTIMAL MANAGEMENT PROBLRM OF FINANCIAL SYSTEM - Viktor, Oliynyk; Korsakova St, Rimskogo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The algorithm for solving of dynamic management problem is examined, that is conducted in a few stages: from discrete initial data we get optimal functional dependence; we find differential equalization of process; we set a management function and criterion of optimality; we conduct the numeral solution of problem. For a solving the method of the Pontryagin maximum principle is used. Equalization of the state we write regarding Gross Domestic Product. An optimal management of United Kingdom system state from initial to the set end position is offered.